A review on Halal food products and services in Malaysia: impact of food safety standards and regulations - Wahid, Zaharah (International Institute for Halal research and Training (INHART) & Halal Institute Prince of Songkla University, 2018)
No one can deny that standards are vital and important tool for the development of industries and trade. Food standards and technical regulation are aimed at protecting consumer's health, increasing economic viability, and fair trade. This paper examines the halal food industry revolution in terms of voluntary standards and technical regulations. The obligation to adopt international standards included in the Technical Barriers to Trade (TBT) Agreement of the world trade organization (WTO) has influenced the policies of many nations for standardization and serves as a benchmark for international harmonization which guarantees the trade of safe food. This paper also concentrates on the principle of quality assurance in food processing as an essential discipline to guarantee safe, wholesome and functional products. Hazard analysis and critical control points (HACCP), good manufacturing practice (GMP) and good hygiene practice (GHP) are major components of the safety management system in the halal food products and services. Principally, "a hazard" is a biological, chemical or physical agent in, or condition of, food that has the potential to cause an adverse health effect. The likelihood of occurrence and severity of the same is important for the assessment of the risk presented by the hazard to the food supply chain. This paper highlights the impact of standards and regulation on halal products and services.